Assessment of clinical data on urocortins and their therapeutic potential in cardiovascular diseases: A systematic review and meta‐analysis. Issue 6 (11th August 2021) - Kovács, Dóra K.; Farkas, Nelli; Soós, Alexandra; Hegyi, Péter; Kelava, Leonardo; Eitmann, Szimonetta; Schekk, Anna; Molnár, Zsolt; Erőss, Bálint; Balaskó, Márta
Abstract: Heart failure (HF) and cardiovascular diseases present public health challenges. Although great progress was achieved in their treatment, there is continuous need for new therapies. Urocortins of the corticotropin neuropeptide family were reported to exert beneficial effects in animal models of HF and cardiovascular diseases. We aimed to assess the available clinical evidence on the potential role of urocortins in HF and other cardiovascular diseases. We explored MEDLINE, Embase, CENTRAL, and Scopus databases. Twenty‐seven studies were included in the qualitative and 15 studies (2005 patients) in the quantitative syntheses. Available data allowed us to meta‐analyze the blood pressure (BP) lowering and heart rate (HR) increasing effects of urocortin 2 in HF with reduced ejection fraction. We applied meta‐regression to explore the association between left ventricular ejection fraction and serum urocortin 1 and urocortin 2 levels. Short‐term urocortin 2 infusion decreased mean arterial pressure in chronic HF with reduced ejection fraction (mean difference = −9.161 mmHg, 95% confidence interval [CI] −12.661 to −5.660 mmHg, p  < 0.001). Such infusions increased HR mildly (mean difference = 5.629 beats/min, 95% CI 1.612 to 9.646 beats/min, p  = 0.006). Although some studies reported increased urocortin 1 and urocortin 2 levels in HF with growing severity, our meta‐regressions failed to confirm associations between blood urocortin levels and left ventricular ejection fraction. Clinical evidence confirms short‐term BP lowering effects of urocortin 2, whereas individual studies report additional beneficial effects. Further clinical investigations are necessary to confirm the latter and the long‐term value of these peptides in cardiovascular diseases. Review protocol: CRD42020163203.